Effect of column dimension on the punching shear capacity of concrete slabs reinforced with GFRP bars - Junaid M. Talha; Awad Raghad; Barakat Samer; Metawa Abdulrahman (E3S Web of Conferences, 2024)
Traditional steel reinforcements are highly susceptible to corrosion affecting their durability and leading to structural weaknesses. The use of GFRP bars offers a corrosion-resistant alternative, potentially extending the lifespan and durability of concrete structures. With this in mind, the current research looks at the efficiency of GFRP bars towards the punching shear capacity of slabs. This study, in specific, explores the effect of column size on the punching shear capacity of glass fiber-reinforced polymer (GFRP) reinforced square concrete slabs. The research involves square concrete slabs (1500×1500 mm) reinforced with GFRP bars, which were centrally loaded until failure. Parameters like the ultimate load capacity, crack patterns, strain development in the GFRP bars and concrete, and critical punching shear area were assessed to evaluate the slabs’ behavior. The punching shear area measured at failure was notably larger than the distance specified by design codes.